Educative Game Training for PKK Woman in Bulakan District Sukoharjo - Aldila Fitri Radite Nur Maynawati (ASEAN Journal of Empowering Community, 2021)
Partner address in Bulakan District Sukoharjo, Sukoharjo Regency. The problem of partners known from the interviews on the woman of Bulakan villagers, especially residents of RT 03 RW 09, is that the social situation in the area still lacks socialization in children who addict to gadgets. But parents have various jobs, but most of their livelihoods are factory workers. So the interaction between parents and children is very lacking. The number of children who play games on gadgets that parents use for educational games will be something that can develop creativity in children. Through this devotion, the target is PKK woman can be learning in children. Later, children can imply the learning that has been obtained and can add insight. The target of this community service is educative game training. The resulting product is an educative game guide. The product implemented is an educative game guide. The use of media in implementing this devotion is projectors, laptops, power points, cameras, or video shooting. There will be stages of educative games in the guide, starting from preparing facilities and infrastructure, allocating time or schedule, and implementation.